On trees with a special proper partial o-1 colorings - Vahan V. Mkrtchyan (Изд-во НАН РА)
It is proved that in a tree in which the distance between any two endpoints is even,there is a maximum proper partial 0¡1 coloring such that the edges colored by 0 form a maximum matching.
Keywords: Mathematics